Online Health Forums and Services: Benefits, Risks and Perspectives - Mano, Rita (Bentham Science Publishers, 2021)
The internet provides a major source of exchanging health information through online portals and new media. Internet users can access health sites and online forums to obtain health information. In turn, these information sources act as a catalyst for wellbeing and improving personal health care behaviors and routines. Competent health institutions encourage the development of these individual behaviors that enable individuals to increase health empowerment and to take responsibility for their own health needs, diagnosis and treatment. Online Health Forums and Services: Benefits, Risks and Perspectives is an investigation of the use of online health forums and services. The author first introduces the reader to the theories that define online social behaviors in terms of health care services. The chapters following this introduction attempt to account for the variations in online health care portal use and to what extent does social networking induce variations in health behaviors grounded in theory. A summary of media used for affecting health behavior change is also provided along with a discussion of the socioeconomic attributes of the individuals most likely to be affected in terms of their health behaviors. The book provides a comprehensive perspective that links the aspects of the micro-level use of the Internet for health purposes (accessing health related websites, participation in health forums and networking sites) to the macro level practices of telemedicine. Readers will be able to understand the social and health characteristics of the different groups of patients and estimate the extent to which individuals in need of health and medical information are taking advantage of the availability of information and communication platforms to improve their health, or if they are being left behind. This is a timely reference for healthcare professionals, researchers and consultants involved in digital health care initiatives and public health administration who are seeking information about how access to online health information can influence lifestyles in a way that impacts human behavior in a positive, meaningful way.